The closest equivalent in Indonesian for the Japanese verbs 'to wear (clothes)' - Oeinada, I Gede (International Seminar on Austronesian Languages and Literature; Vol 9 No 1 (2021): PROCEEDINGS International Seminar on Austronesian Languages and Literature IX (ISALL IX), 2021)
Several Japanese verbs mean 'to wear (clothes)' and, when translated into Indonesian, usually can be translated into the same word memakai 'to wear/to put on'. This phenomenon deserves further investigation to gain a better understanding, particularly in terms of determining the best closest equivalent for these verbs in Indonesian. In this paper, the data was collected using the linguistic corpus method, and the theory used was the NSM semantic theory. The result demonstrates that each of these synonymous verbs has distinct meaning components that can be used to distinguish one from another. On the other hand, the Indonesian language lacks the richness of Japanese verbs that mean 'to wear (clothes).' As a result, when translating into Indonesian, general words are being used